2017
DOI: 10.3892/mmr.2017.6204
|View full text |Cite
|
Sign up to set email alerts
|

CD164 regulates proliferation and apoptosis by targeting PTEN in human glioma

Abstract: Cluster of differentiation 164 (CD164), a sialomucin, has been demonstrated to be involved in the regulation of proliferation, apoptosis, adhesion and differentiation in multiple cancers. CD164 is regarded to be a potential promotor of tumor growth. However, the involvement of CD164 in human glioma proliferation and apoptosis remains unknown. The aim of the present study was to investigate the expression and oncogenic function of CD164 in normal human astrocytes (NHA) and glioma cells in vitro and in vivo. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Moreover, these genes were also involved in the oncogenic progression of primitive neuroectodermal tumor in IPA analysis. Another gene involved in multiple cancers, CD164, has been reported to promote glioma via the tumor-suppressor PTEN [ 119 ]. These data suggest that FOXP2 may have the capacity to repress both pro-oncogenic and tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these genes were also involved in the oncogenic progression of primitive neuroectodermal tumor in IPA analysis. Another gene involved in multiple cancers, CD164, has been reported to promote glioma via the tumor-suppressor PTEN [ 119 ]. These data suggest that FOXP2 may have the capacity to repress both pro-oncogenic and tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%
“…As a multifunctional protein, CD164 acted as a surface marker of hematopoietic stem cells, a CXCR4 promoter activity‐enhancing transcription factor, and a stem cell‐specific marker inducer 9, 10, 11. High expression of CD164 was found in several malignant diseases and was associated with clinical outcomes of patients 13, 23, 28, 29, 30, 31. In lung cancer, the positive associations were significantly existed between CD164 expression and tumor size, tumor cell grading, and lymph node involvement 14.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have revealed that CD164 was involved in tumor progression via the regulation of cell proliferation and apoptosis in several cancers 13, 14, 15, 23, 32. In addition, CD164 was implicated in regulating the migration and invasion of lung cancer and medulloblastoma cells 17, 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations